411 Effects of tannin treatment on pathogen control and nitrogen metabolism in composted poultry litter. (7th December 2018) - Arzola, C; Anderson, R; Hume, M; Min, B; Nisbet, D; Ruiz-Barrera, O; Castillo-Castillo, Y; Salinas-Chavira, J; Ontiveros-Magadan, M; Corral-Luna, A; Copado-Garcia, R; Estrada-Gandarilla, M
Abstract: Poultry litter (PL) contains uric acid which makes it a good crude protein supplement for ruminants. However, PL must be treated to kill pathogens before feeding. Composting effectively kills pathogens but risks loss of ammonia due to uric acid degradation. Because tannins possess antimicrobial activity and can inhibit uric acid metabolism, we tested their ability to preserve uric acid and reduce pathogens during PL composting. Used PL (76% DM) was mixed 2:1 with 0.4 M phosphate buffer (pH 6.5) and distributed (11 g) to 50-mL tubes (3/treatment per sample day) amended with 1 mL buffer alone or containing pine bark, quebracho, chestnut or mimosa tannins to achieve 1.5% wt/vol. Tubes were inoculated with a novobiocin- and naladixic acid-resistant Salmonella Typhimurium (STNN), closed with caps and incubated at successive 3 day increments at 22oC, 37oC and 42oC, respectively. Repeated measures analysis of variance of bacterial numbers enumerated in contents collected on days 0, 6 and 9 revealed a main effect of day (P < 0.0001) but not treatment (P > 0.05) on all populations, with initial counts of E. coli and STNN being decreased from 4.3 and 3.6 log10 CFU/g to below detection limits (1 log10 CFU/g) by day 9. A tendency for a day x treatment interaction was observed on STNN populations (P = 0.09), with STNN being decreased 0.4 log10 CFU/g on day 6 in quebracho-treated litter compared to being increased 0.6 log10 CFU/g in control PL. Analysis of ammonia, urea and uric acid concentrations revealed an effect of day (P < 0.05) but not treatment or their interaction, with concentrations increasing 36, 32 and 27% from initial values (2.9, 3.3 and 4.4 µmol/mL, respectively). Results confirm that composting was an effective pathogen control treatment but revealed little additional benefit due to tannin treatment under the conditions studied here.